2014
DOI: 10.1007/s00040-014-0362-6
|View full text |Cite
|
Sign up to set email alerts
|

Myrmica ants host highly diverse parasitic communities: from social parasites to microbes

Abstract: Myrmica ants have been model species for studies in a variety of disciplines, including insect physiology, chemical communication, ant social dynamics, ant population, community ecology, and ant interactions with other organisms. Species belonging to the genus Myrmica can be found in virtually every habitat within the temperate regions of the northern hemisphere and their biology and systematics have been thoroughly studied. These ants serve as hosts to highly diverse parasitic organisms from socially parasiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
52
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(54 citation statements)
references
References 118 publications
(138 reference statements)
0
52
0
Order By: Relevance
“…Myrmica ants can be hosts to many parasitic organisms from several taxonomic groups including ecto-and endoparasitic fungi and other microbial pathogens, such as: R. wasmannii; Beauveria bassiana (Bals. (Radchenko and Elmes 2010, Simmons et al 2015, Witek et al 2014). In particular, M. scabrinodis is common in Europe (Czechowski et al 2012, Radchenko and Elmes 2010, Seifert 2007, frequently parasitized by R. wasmannii (Espadaler and Santamaria 2012) and other (social) parasites (Tartally 2008, Witek et al 2014.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Myrmica ants can be hosts to many parasitic organisms from several taxonomic groups including ecto-and endoparasitic fungi and other microbial pathogens, such as: R. wasmannii; Beauveria bassiana (Bals. (Radchenko and Elmes 2010, Simmons et al 2015, Witek et al 2014). In particular, M. scabrinodis is common in Europe (Czechowski et al 2012, Radchenko and Elmes 2010, Seifert 2007, frequently parasitized by R. wasmannii (Espadaler and Santamaria 2012) and other (social) parasites (Tartally 2008, Witek et al 2014.…”
Section: Introductionmentioning
confidence: 99%
“…(Radchenko and Elmes 2010, Simmons et al 2015, Witek et al 2014). In particular, M. scabrinodis is common in Europe (Czechowski et al 2012, Radchenko and Elmes 2010, Seifert 2007, frequently parasitized by R. wasmannii (Espadaler and Santamaria 2012) and other (social) parasites (Tartally 2008, Witek et al 2014. Myrmica scabrinodis is a mesothermo-and mesohygrophilic species of different kinds of humid habitats, which is tolerant of soil moisture but avoids expressly xerothermal habitats.…”
Section: Introductionmentioning
confidence: 99%
“…Line 175-176: "In the larger region, former studies have shown M. gallienii to be occasionally infected (see Csata et al, 2013), while M. schencki has never been found to be infected (see Witek et al, 2014)." -this is discussion, not results!…”
Section: Rmentioning
confidence: 96%
“…R: Line 246 Explain how the fungus and its interaction with the ant could be of importance for the Maculinea butterflies A:We introduced an explanatory sentence, thus the section is as follows: "Data on the epidemiology of R. wasmannii bears a conservational relevance as well, since its host ant M. scabrinodis also nurses caterpillars of the socially parasitic Maculinea butterflies that are strictly protected all over Europe (see Witek et al, 2014). The reduced lifespan of infected host ants (Csata et al, 2013) might be relevant for the protection of Maculinea, since it could negatively influence the survival rate of parasitic Maculinea caterpillars as well."…”
Section: Rmentioning
confidence: 99%
See 1 more Smart Citation